A comparative study of intertan nail versus proximal femoral nail antirotation in the treatment of peritrochanteric fractures - Kothiyal, Pranav; Vij, Kunal; Gupta, Puneet; Sharma, Shashank (International Journal of Research in Orthopaedics, 2022)
Background: Over the past decades the incidence of intertrochanteric fractures has increased and there is a universal agreement about the intramedullary nail being the preferred implant of fixation for these fractures. Methods: In this study we have attempted to assess and compare the results and immediate as well as long term outcome of fractures managed by proximal femoral nail anti rotation and the intertan nail. We included 102 patients in our study, half in the group managed by proximal femoral nail anti rotation group and half in the group managed by intertan nail. Over a period of almost one and half years we evaluated the patients in immediate and late post op period for the union of the fracture, functional outcomes and the short- and long-term complications. Results: The results were evaluated in the terms of intraoperative variables like fluoroscopy time, mean blood loss and reduction achieved and postoperatively in terms of superficial wound infections and Harris hip score and mobility score of paper and palmer which were comparable for both groups of patients with slight differences in some variables. Conclusions: We concluded that the intertan nail is a good option for fracture fixation in patients with unstable intertrochanteric fractures and though associated with a steeper learning curve it has lesser complications and slightly better functional outcomes as compared to the proximal femoral nail anti rotation.